Description of a rat palatal acrylic plate that can be relined - Meister, Lissandra Matos Bról; Bail, Michele; Pellissari, Cláudia Viviane Guimarães; Ban, Manuella de Cássia Iglesias; Campagnoli, Eduardo Bauml; Jorge, Janaina Habib [UNESP]; Campanha, Nara Hellen (Wiley, 2014)
Purpose: The objective of this article is to describe a method to construct an intraoralacrylic device that permits a reline material to be added to the inner surface of thepalatal plate.Materials and Methods: Fifteen 60-day-old adult female rats (Rattus NorvegicusAlbinus Wistar), weighing 150 to 250 g were used for this study and allocated to threegroups (n = 5): G1, animals wearing a heat-polymerized acrylic resin palatal plate(Lucitone 550) for 14 days; G2, animals wearing a heat-polymerized acrylic resinpalatal plate (Lucitone 550) relined with Tokuyama Rebase II for 14 days; and G3,animals maintained under the same conditions as the experimental groups, withoutwearing palatal plates for 14 days. The manipulation of the animals followed theguidelines of the Brazilian College of Animal Experimentation, under the approval ofthe animal ethics committee of the State University of Ponta Grossa. The palatal platescovered the whole palate, were fixed in the molar region with light-cured resin, andwere kept there for 14 days. The animals received a paste diet and water ad libitum.Before and after the trial period, the rats were weighed individually on a precisionscale. Statistical analysis was performed using a two-way analysis of variance (α =0.05) test for comparison of the animals’ weight (g) at time 0 and after 14 days ofusing the palatal plate.Results: No statistical differences were observed regarding the weight of the animalsamong the experimental groups in the study.Conclusions: The individual master impressions, the molar teeth coverage, and themethod of cementation with nonadhesive composite resin provided good stability forthe palatal plate showed in this study, not disturbing the eating habits and nutritionof the animals. This model seems reproducible, offering adequate histopathologicalevaluation. Differences in tissue morphology exist between the animals that used thepalatal plate and the animals that did not use this device. Use of these palatal platescould clarify how prostheses bring changes in the palatal mucosa of users.
Keywords: Denture